A 6.5-year clinical follow-up of direct resin composite buildups in the posterior dentition: Introduction of a new minimally invasive restorative method. Issue 10 (October 2015) - Staehle, Hans Joerg; Wohlrab, Theresa; Saure, Daniel; Wolff, Diana; Frese, Cornelia
Abstract Objectives Restorative rehabilitation of missing single teeth in the posterior dentition is achieved primarily by dental implants or fixed dental prostheses. Here we introduce an uncommon, minimally invasive treatment option in order to close single tooth gaps. Methods The purpose of this study was to evaluate the clinical quality and survival of 45 direct composite buildups in the posterior dentition. A detailed clinical examination was performed, and restorations were rated qualitatively using the modified USPHS/FDI criteria. Results The mean extension of the direct composite buildups was 2.96 (1.12) mm per tooth. Interdental closures from both adjacent teeth had a significantly higher extension of the direct composite buildups than one-sided interdental closures (p = 0.03). Patients with a history of prior tooth loss showed a significantly greater extension of direct composite buildups than patients without prior tooth loss (p = 0.006). During the follow-up period, no restoration showed unfavorable events. The overall survival rate for the direct composite buildups was 100% after median follow-up of 78.96 months. The clinical quality rating indicated that most of the restorations (>94%) displayed excellent or good quality. No periodontal destruction, signs of gingival inflammation or increased plaque accumulation was observed. Conclusions The posterior direct composite buildups evaluated in this study showed promising clinical survival data and excellent quality parameters after a median observation time of 6.5 years. Clinical Significance If a minimally or non-invasive treatment approach is indicated, posterior direct composite buildups provide a successful treatment alternative for the closure of single-tooth gaps to implant-supported or fixed dental prostheses.